1996
DOI: 10.1088/0031-9155/41/9/007
|View full text |Cite
|
Sign up to set email alerts
|

Response analysis of TLD-300 dosimeters in heavy-particle beams

Abstract: In vivo dosimetry is recommended as part of the quality control procedure for treatment verification in radiation therapy. Using thermoluminescence, such controls are planned in the p(65) + Be neutron and 85 MeV proton beams produced at the cyclotron at Louvain-La-Neuve and dedicated to therapy applications. A preliminary study of the peak 3 (150 degrees C) and peak 5 (250 degrees C) response of CaF2:Tm (TLD-300) to neutron and proton beams aimed to analyse the effect of different radiation qualities on the do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 23 publications
4
27
0
Order By: Relevance
“…Their data were related to absorbed dose to muscle tissue. Loncol et al (1996) measured peak efficiencies (relative to absorbed dose to water) for an 85 MeV proton beam, thereby complementing the findings of this work in qualitatively good agreement. An in-depth intercomparison of TLD-300 efficiencies determined by different authors can be found in Berger and Hajek (2007).…”
Section: Relative Tl Efficiencysupporting
confidence: 78%
See 1 more Smart Citation
“…Their data were related to absorbed dose to muscle tissue. Loncol et al (1996) measured peak efficiencies (relative to absorbed dose to water) for an 85 MeV proton beam, thereby complementing the findings of this work in qualitatively good agreement. An in-depth intercomparison of TLD-300 efficiencies determined by different authors can be found in Berger and Hajek (2007).…”
Section: Relative Tl Efficiencysupporting
confidence: 78%
“…Considering the non-uniform pattern of dose deposition at the microscopic level, the enhanced sensitivity of peak 5 to HCP irradiation can be explained by its linear-supralinear dose response (Olko, 1998(Olko, , 2007. Several authors have proposed to exploit this increased sensitivity to high linear energy transfer (LET) radiation for neutron-gamma ray discrimination (Loncol et al, 1996) and HCP dosimetry (Hoffmann and Prediger, 1983;Loncol et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…The different peaks in the glow curves of certain TLD materials show different sensitivities to the LET of the incident radiation. Correspondingly, the relative peak intensity can be used to measure the LET in mixed radiation fields or heavy particle beams …”
Section: Specific Applicationsmentioning
confidence: 99%
“…Correspondingly, the relative peak intensity can be used to measure the LET in mixed radiation fields 125,126 or heavy particle beams. 127…”
Section: C Proton and Ion Beamsmentioning
confidence: 99%
“…Proton LET is notoriously difficult to measure directly with only a very limited number of devices commercially available such as the tissue-equivalent proportionality counter (TEPC), 19 silicon spectrometer, 20 or CR-39 etch detectors. 21 Other authors have presented creative strategies for simultaneous proton dose and LET measurements such as the use of organic scintillators, 22 thermoluminescent dosimeters 23,24 (TLDs), Al 2 O 3 :C OSLD 25 detectors, and Gafchromic EBT3 films. 26 In this work, we present a novel solution to this problem by proposing the use of a proton energy dependent high Z eff storage phosphor (Z eff = 49, BaFBr 0.85 I 0.15 :Eu 2+ ) in conjunction with a near-proton energy independent low Z eff storage phosphor (Z eff = 18, KCl:Eu 2+ ).…”
Section: Introductionmentioning
confidence: 99%